Dyslipidemia in Childhood Obesity: A Review (Bangladesh Journal of Child Health, 2018)
Childhood obesity has become epidemic in developed as well as developing countries. Apart from genetic factors, changes of lifestyle like consumption of excess calorie rich food, lack of physical activity and increased screen time are major contributing factors for childhood obesity. Many co-morbid conditions like cardiovascular, metabolic, neurological, hepatic, pulmonary, orthopedic, and renal disorders are associated with childhood obesity. It has both immediate medical complications as well as long term health consequences in later life. The most hazardous consequences like the cardiovascular disorder occur due to early athrosclerotic process which is accelerated due to dyslipidemia. As a result dyslipidemia is an important etiologic factor for development of cardiovascular disease (CVD), which is a leading cause of death in adulthood throughout the world. As abnormal vascular changes begins in childhood, and as dyslipidemia is an significant risk factor for CVD, screening and treatment of dyslipidemia in obese children and adolescents are an important health issue to prevent development metabolic syndrome and its consequences.Bangladesh J Child Health 2018; VOL 42 (3) :148-154